FACTORS INFLUENCING THE IMPLEMENTATION OF THE INNOVATION STRATEGY AT INDUSTRIAL ENTERPRISES - Yuldasheva Nilufar Abduvakhidovna (Scholar Express Journals, 2023)
The article discusses approaches to the formation of an innovative strategy for the development of an enterprise. Choosing the right innovation strategy is an important part of an organization's activities. There are a big number of internal and external factors. They have a great influence on the formation of an innovative strategy. It is important to highlight the correct factors. This article reviews experts’ classifications and suggests an additional classification of factors, which can influence choosing an innovation strategy.
Keywords: strategy; innovation strategy; innovative development; infrastructure